2021
DOI: 10.3389/fpsyg.2021.666166
|View full text |Cite|
|
Sign up to set email alerts
|

Intra-specific Variation in the Social Behavior of Barbary macaques (Macaca sylvanus)

Abstract: Non-human primates show an impressive behavioral diversity, both across and within species. However, the factors explaining intra-specific behavioral variation across groups and individuals are yet understudied. Here, we aimed to assess how group size and living conditions (i.e., captive, semi-free-ranging, wild) are linked to behavioral variation in 5 groups of Barbary macaques (N=137 individuals). In each group, we collected observational data on the time individuals spent in social interactions and on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
(117 reference statements)
3
2
0
Order By: Relevance
“…Our results are in stark contrast with previous reports on prosocial preferences in captive Japanese macaques ($0%, 15 ). Consistent with the prediction that independently breeding free or semi free-ranging primates have lower social tolerance than captive populations, [71][72][73][74] our study group showed lower grouplevel social tolerance (Pielou's J 0 = 0.13) than the previously tested population residing in a more restricted captive setting (Pielou's J 0 = 0.32). 15 It must be noted that our group-level tolerance measure was limited to focal individuals and not the entire population.…”
Section: Between-group Variation In Japanese Macaques' Prosocial Tend...supporting
confidence: 88%
“…Our results are in stark contrast with previous reports on prosocial preferences in captive Japanese macaques ($0%, 15 ). Consistent with the prediction that independently breeding free or semi free-ranging primates have lower social tolerance than captive populations, [71][72][73][74] our study group showed lower grouplevel social tolerance (Pielou's J 0 = 0.13) than the previously tested population residing in a more restricted captive setting (Pielou's J 0 = 0.32). 15 It must be noted that our group-level tolerance measure was limited to focal individuals and not the entire population.…”
Section: Between-group Variation In Japanese Macaques' Prosocial Tend...supporting
confidence: 88%
“…Our results are in stark contrast with previous reports on prosociality in captive Japanese macaque (∼ 0%, (10)). Consistent with the prediction that independently breeding free or semi free-ranging primates have lower social tolerance than captive populations (5962), our study group showed lower group-level social tolerance (0.13) than the previously tested population residing in a more restricted captive setting (0.32) (10). It must be noted that our group level tolerance measure was limited to focal individuals and not the entire population.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are in stark contrast with previous reports on prosocial preferences in captive Japanese macaques (∼0%, 15 ). Consistent with the prediction that independently breeding free or semi free-ranging primates have lower social tolerance than captive populations, 71 , 72 , 73 , 74 our study group showed lower group-level social tolerance (Pielou’s J′ = 0.13) than the previously tested population residing in a more restricted captive setting (Pielou’s J′ = 0.32). 15 It must be noted that our group-level tolerance measure was limited to focal individuals and not the entire population.…”
Section: Discussionsupporting
confidence: 89%